The product of the factors in the given expression comes to be
.
The given expression is:
![(1.466*10^{-8} )(5.02*10^5)](https://tex.z-dn.net/?f=%281.466%2A10%5E%7B-8%7D%20%29%285.02%2A10%5E5%29)
We can rewrite the given expression as
![(1.466*5.02)(10^{-8} *10^5)](https://tex.z-dn.net/?f=%281.466%2A5.02%29%2810%5E%7B-8%7D%20%2A10%5E5%29)
<h3>What is the exponent addition rule? </h3>
If we have two numbers with the same base we can write the product of the numbers as a single base followed by the addition of exponents.
![a^m*a^n = a^{m+n}](https://tex.z-dn.net/?f=a%5Em%2Aa%5En%20%3D%20a%5E%7Bm%2Bn%7D)
![1.466*5.02=7.35932](https://tex.z-dn.net/?f=1.466%2A5.02%3D7.35932)
....from exponent addition rule
So, ![(1.466*10^{-8} )(5.02*10^5)=7.35932 *10^{-3}](https://tex.z-dn.net/?f=%281.466%2A10%5E%7B-8%7D%20%29%285.02%2A10%5E5%29%3D7.35932%20%2A10%5E%7B-3%7D)
Therefore, the product of the factors in the given expression comes to be
.
To get more about exponents visit:
brainly.com/question/819893